LIFESTYLE INTERVENTIONS IN THE MANAGEMENT OF ENDOMETRIOSIS-ASSOCIATED PAIN: A NARRATIVE REVIEW - Karolina Orda; Karolina Niewola; Kamil Arciszewski; Natalia Hariasz; Philip Kłakowicz; Jakub Szumiło; Klaudia Kasperska; Mariana Markiv; Michał Słowik; Paweł Stenzel (International Journal of Innovative Technologies in Social Science, 2026)
Endometriosis is a chronic inflammatory condition associated with significant pain, reduced quality of life, and functional impairment. Although pharmacological and surgical treatments remain the standard of care, increasing attention has been directed toward lifestyle and non-pharmacological interventions as supportive management strategies. The aim of this narrative review was to evaluate the role of physical activity, dietary interventions, physiotherapy, and psychological approaches in the management of endometriosis-associated pain.A literature search was conducted using major electronic databases, including PubMed, Scopus, and Web of Science, focusing on studies examining non-pharmacological interventions in women with endometriosis. Both interventional and observational studies, as well as systematic reviews, were included.The available evidence suggests that lifestyle interventions may influence multiple mechanisms involved in endometriosis, including inflammation, hormonal regulation, neuromuscular function, and central pain processing. Physical activity appears to reduce pain and improve psychological well-being, although participation remains limited due to symptom burden. Dietary strategies, particularly anti-inflammatory patterns, may contribute to symptom improvement, while physiotherapy and psychological interventions address functional and emotional aspects of chronic pain. Multimodal approaches appear to provide the most consistent benefits.Despite promising findings, the evidence remains heterogeneous and limited by methodological variability. Lifestyle interventions should be considered as complementary strategies within a multidisciplinary treatment framework. Further high-quality studies are needed to establish standardized clinical recommendations.